2018
DOI: 10.21109/kesmas.v13i2.1223
|View full text |Cite
|
Sign up to set email alerts
|

Role Stress, Personality Types, Burnout, and Performance of Midwives in the Achievement of Postnatal Care Program in Surabaya

Abstract: The coverage of postnatal care program in Surabaya had declined since 2011–2013 and could not reach the target. This analytic study with an observational approach and a cross-sectional design was conducted during April–May 2015 to analyze the effect of role stress, personality types, and burnout on midwives’ performance in the achievement of postnatal care program in Surabaya. A total sample of 45 midwives was collected from eight public health care centers in Surabaya with basic emergency obstetric and neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Burnout and stress were identified as a threat to workforce sustainability [37,[108][109][110]. Higher rates of burnout were reported to be trending in younger midwife populations and those who did not perceive adequate pay in one Indonesian study [115].…”
Section: Plos Onementioning
confidence: 99%
“…Burnout and stress were identified as a threat to workforce sustainability [37,[108][109][110]. Higher rates of burnout were reported to be trending in younger midwife populations and those who did not perceive adequate pay in one Indonesian study [115].…”
Section: Plos Onementioning
confidence: 99%
“…There are many factors that affected the performance, however, based on the empirical evidences showed that the most dominant factor that affects the performance of midwife is personality type (Halimsetiono et al, 2018). One of the personality types that is able to increase performance is proactive personality.…”
Section: Introductionmentioning
confidence: 99%